SAT0464 Remission at 6 as well as at 9 months predicts good long-term outcome in early rheumatoid arthritis patients with non-biological treatment. (23rd January 2014) - Britsemmer, K.; Tuyl, L.H.V.; Schaardenburg, D.V.; Boers, M.
Abstract : Background: Recently, an American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) collaboration redefined remission in rheumatoid arthritis (RA). Objectives: To validate if remission predicts later good long-term outcome in terms of radiological progression and physical functioning in an early arthritis cohort. Methods: Patients from the Amsterdam Jan van Breemen Research Institute with RA (1987 ACR criteria), and not using biologicals, were included in the analysis. ACR/EULAR remission status (Boolean) was evaluated at 6 and 9 months. Long-term outcome included radiographs of hands and feet (scored by the Sharp- van der Heijde (SvH) method) and the health assessment questionnaire (HAQ). Good long-term outcome was defined as 1) stable X-ray score (change <1 in SvH), 2) low score on the HAQ (HAQ change ≤0 AND HAQ score consistently ≤0.5) and 3) both stable X-rays scores AND stable low HAQ scores between year 1 and 2 and between year 2 and 3. To analyze the ability of remission to predict good long-term outcome likelihood ratios and logistic regression were used. Results: We studied 359 patients with mean age 54 (SD 13), 70% female, median symptom duration 6 (3-7) months, and median swollen joint count and tender joint count 8 (4-11) and 6 (3-10), respectively. Mean DAS28 was 5, 1 (1, 2). Six percent of patients reached remission at 6 months, while 24% of all patients were in minimal disease activity state defined as DAS28<2.6. At 9 months these proportions were 11% and 25%, respectively. In the second year after inclusion 43% of the patients had radiographic progression (median progression 3 [2-8]). Between year 2 and 3 37% had radiographic progression (median progression 3 [2-6]). In 35% HAQ outcomes were good and in 20% both long-term outcomes were good between year 1 and 2. Between year 2 and 3 these proportions were 32% and 21%, respectively. Patients in remission at 9 months, but not at 6 months, had a significantly increased likelihood of a good outcome in terms of stable HAQ and stable HAQ/Sharp between year 1 and 2 (table 1 ). Furthermore, remission at 6 as well as at 9 months was significantly predictive for good outcome in terms of stable HAQ and stable HAQ/Sharp between year 2 and 3 (table 1 ). Conclusions: In this early RA cohort not on biological treatment, good long-term outcome in terms of radiological progression and physical functioning between year 1 and 2 after inclusion was predicted by remission at 9 months, and between year 2 and 3 after inclusion by remission at 6 as well as at 9 months. Disclosure of Interest: None Declared